PHYSICAL FUNDAMENTALS OF NON-CONNECTIVE ENERGY SOURCES IN TEACHING PHYSICS IN GENERAL SECONDARY EDUCATION - Mirzamuratov Bahodir Fayzullaevich; Karabaev Ibragim Turdievich (Galaxy International Interdisciplinary Research Journal, 2021)
This article summarizes information on solar photovoltaic and solar engineering elements in a school physics course, taking into account their age, ability, and class stages so that students can adequately master the information in the physics course program in physics teaching in general secondary schools. Taking into account the information presented in the article, it is a practical approach for students to acquire knowledge, skills and abilities on the physical basis of modern solar photoelectronics. The basics of applying the principle of consistency of a broader interpretation of data on solar photovoltaic cells and elements of solar technology in the teaching of physics are described.